NEW INNOVATION USING TOPICAL ITRACONAZOLS AS A SUPERFICIAL FUNGAL SKIN INFECTION THERAPY AND ITS SUPERIORITY COMPARED TO STANDARD THERAPY - Tan, Sukmawati Tansil; Firmansyah, Yohanes (Perhimpunan Kesehatan Holistik Indonesia, 2021)
Background: Fungal infection of the skin is a common clinical problem in the community, particularly in groups of people who practice poor hygiene or in populations with a low immune status. Microsporon audoinii and Trichophyton rubrum, can cause the disease to be chronic and residif. This is generally due to the fungus developing a mechanism of resistance to the commonly used drug regimens in the community. As a result, a novel innovation is required to expedite patients' healing from dermatophytosis. Method: The purpose of this study is to compare the efficacy of a new treatment therapy utilizing a combination of 2% itraconazole, 1% salicylic acid, and 2% sulfur to that of 2% ketoconazole (standard therapy). The samples for this study were all cases of fungal infections of the skin diagnosed at Indra's clinic between 2016 and 2017. The study's independent variable was the formulation of the drug, while the dependent variable was clinical improvement and the occurrence of side effects. Results: The cure rate was 91,7 percent for the 121 respondents who received a combination cream containing 2% itraconazole, and 80.7 percent for the 114 respondents who received a ccream containing 2% ketoconazole. There were no statistically significant differences in adverse events between the two intervention groups. Finally, Innovative drug formulations for fungal infections (2 percent itraconazole, 1% salicylic acid, and 2% sulfur) have been shown to be more effective and superior to standard therapy.